Microbial community composition explains soil respiration responses to changing carbon inputs along an Andes‐to‐Amazon elevation gradient. (19th May 2014) - Whitaker, Jeanette; Ostle, Nicholas; Nottingham, Andrew T.; Ccahuana, Adan; Salinas, Norma; Bardgett, Richard D.; Meir, Patrick; McNamara, Niall P.; Austin, Amy
Summary The Andes are predicted to warm by 3–5 °C this century with the potential to alter the processes regulating carbon (C) cycling in these tropical forest soils. This rapid warming is expected to stimulate soil microbial respiration and change plant species distributions, thereby affecting the quantity and quality of C inputs to the soil and influencing the quantity of soil‐derived CO2 released to the atmosphere. We studied tropical lowland, premontane and montane forest soils taken from along a 3200‐m elevation gradient located in south‐east Andean Peru. We determined how soil microbial communities and abiotic soil properties differed with elevation. We then examined how these differences in microbial composition and soil abiotic properties affected soil C‐cycling processes, by amending soils with C substrates varying in complexity and measuring soil heterotrophic respiration (RH). Our results show that there were consistent patterns of change in soil biotic and abiotic properties with elevation. Microbial biomass and the abundance of fungi relative to bacteria increased significantly with elevation, and these differences in microbial community composition were strongly correlated with greater soil C content and C:N (nitrogen) ratios. We also found that RH increased with added C substrate quality and quantity and was positively related to microbial biomass and fungal abundance. Statistical modelling revealed that RH responses to changing C inputs were best predicted by soil pH and microbial community composition, with the abundance of fungi relative to bacteria, and abundance of gram‐positive relative to gram‐negative bacteria explaining much of the model variance. Synthesis. Our results show that the relative abundance of microbial functional groups is an important determinant of RH responses to changing C inputs along an extensive tropical elevation gradient in Andean Peru. Although we do not make an experimental test of the effects of climate change on soil, these results challenge the assumption that different soil microbial communities will be 'functionally equivalent' as climate change progresses, and they emphasize the need for better ecological metrics of soil microbial communities to help predict C cycle responses to climate change in tropical biomes.